Evaluation of Engineering Changes Based on Variations from the Model of PGE – Product Generation Engineering in an Automotive Wiring Harness. (May 2022) - Albers, A.; Altner, M. M.; Rapp, S.; Valeh, B.; Redinger, H.; Winter, R.
Abstract: Engineering change management is a central part of the product development process. This paper investigates how variations from the PGE - Product Generation Engineering can improve the evaluation of engineering changes from the wiring harness. Engineering changes that occur in an automotive wiring harness development process are analysed in a case study, evaluated in expert interviews with regard to the risk and effort connected to the implementation and compared to the types of variations. Additional influencing factors are discussed. The variations provide an indication on risk and effort.